2016
DOI: 10.1038/nsmb.3181
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the BAM complex and its implications for biogenesis of outer-membrane proteins

Abstract: In Gram-negative bacteria, the assembly of β-barrel outer-membrane proteins (OMPs) requires the β-barrel-assembly machinery (BAM) complex. We determined the crystal structure of the 200-kDa BAM complex from Escherichia coli at 3.55-Å resolution. The structure revealed that the BAM complex assembles into a hat-like shape, in which the BamA β-barrel domain forms the hat's crown embedded in the outer membrane, and its five polypeptide transport-associated (POTRA) domains interact with the four lipoproteins BamB, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

15
232
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(254 citation statements)
references
References 49 publications
15
232
1
Order By: Relevance
“…In terms of anaP2-anaP3, this is in line with earlier findings on BamA, where the C-terminal POTRA domains ecP3-ecP5 were assumed to have a rigid architecture (36). However, recent crystal structures of assembled BAM complexes challenge this assumption (8)(9)(10). In addition, the orientation of anaP2-anaP3 in the x-ray structure is well within this structure bundle, and thus seems to be a good representative of this ensemble.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In terms of anaP2-anaP3, this is in line with earlier findings on BamA, where the C-terminal POTRA domains ecP3-ecP5 were assumed to have a rigid architecture (36). However, recent crystal structures of assembled BAM complexes challenge this assumption (8)(9)(10). In addition, the orientation of anaP2-anaP3 in the x-ray structure is well within this structure bundle, and thus seems to be a good representative of this ensemble.…”
Section: Discussionsupporting
confidence: 88%
“…However, extrapolating the position of ecP5 from known crystal structures of BamA ( (8,9,28,29)), we propose, to our knowledge, a first model for the relation between flexibility and the dimension of the peptidoglycan layer (PGL, Fig. 6).…”
Section: Discussionmentioning
confidence: 97%
“…Recent X-ray crystallography and cryo-EM studies reported the structures of several Omp85 family members, including FhaC, TamA, and BamA (28,(36)(37)(38)(43)(44)(45)(46)(47). Given the conservation of key features, these structures serve as models for Toc75, albeit with low sequence identity (7%, 7%, and 8%, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…The structure reveals that the POTRA domains form an L-shaped structure very similar to BamA, with a unique extended helix within POTRA2 that is not observed in the POTRA domains of BamA and other Omp85 family members (25,28,(35)(36)(37)(38). Based on these unique structural properties, we investigated the contribution of individual POTRA repeats in binding chloroplast precursors.…”
mentioning
confidence: 99%
“…Although the structure of the Bam complex was recently solved by both X-ray crystallography and cryo-EM (13)(14)(15)(16), the mechanism by which it catalyzes the integration of b-barrel proteins into the OM remains poorly understood. The complex has the shape of a top hat in which the BamA bbarrel forms the crown and the POTRA domains together with the lipoproteins form a brim (14,15).…”
mentioning
confidence: 99%